Audiovisual translation and media accessibility: new languages, new forms of transfer - Di Giovanni, Elena (Status Quaestionis, 2024)
This article explores the evolution of audiovisual translation (AVT) and media accessibility research and practice, first of all by locating them within the framework of Translation Studies. After focusing on some of the main tenets that have guided the development of the mother discipline over the past decades, an exploration of the expanding roads taken by audiovisual translation, especially since the inception of media accessibility research, leads us to reflect on the changing nature of both the languages and the translational processes at the core of both. A brief overview of the results obtained from a questionnaire on the education background and the skills required of accessibility professionals across Europe today reinstates the centrality of linguistic and translational competence, in old and new forms. The final section of the chapter brings into the spotlight a series of examples from the practice of accessibility to media and live events today, pinpointing the increasingly diverse and rich nature of communicative codes and transfer strategies involved.